2021
DOI: 10.9734/jpri/2021/v33i34b31847
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Associated Factors among Adult Tetanus Patients Admitted to Jimma University Medical Center: A Retrospective Study

Abstract: Background: Although, tetanus is a vaccine preventable disease mortality remains high. And despite the establishment of intensive care unit in Jimma University Medical Center the overall mortality reaches up to 40%. This study will question why the outcome of patients has not improved despite the improvement in the setup of ICU and tries to come up with possible associated factors that prognosticated the outcome. Objective: The objective of this study will be to assess the outcome and factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…[ 12 ] In this study, only 5 patients had received the vaccine, indicating lower coverage than reported elsewhere. [ 13 , 14 ] The reason is that 89.01% of the patients in this study are farmers, 94.51% live in rural areas, 75.82% are middle-aged and elderly people. The low vaccination rate is attributed to the inadequate medical resources and insufficient awareness of prevention among middle-aged and elderly individuals in rural areas.…”
Section: Discussionmentioning
confidence: 95%
“…[ 12 ] In this study, only 5 patients had received the vaccine, indicating lower coverage than reported elsewhere. [ 13 , 14 ] The reason is that 89.01% of the patients in this study are farmers, 94.51% live in rural areas, 75.82% are middle-aged and elderly people. The low vaccination rate is attributed to the inadequate medical resources and insufficient awareness of prevention among middle-aged and elderly individuals in rural areas.…”
Section: Discussionmentioning
confidence: 95%